Contributions to sensory physiology. - Neff, William D. (William Duwayne) (Academic Press, 1967)
Contributions to Sensory Physiology: Volume 2 presents the scientific research on the sensory systems. It discusses the physiological basis of sensation. It addresses the evolution of vertebrate hearing. Some of the topics covered in the book are the origins of neocortex; the differentiation of sensory thalamo-cortical systems in early phases of mammal evolution; the predominance of the auditory system in carnivore; effects of brain stem lesions on the normal prepotency of sound; the logarithmic intensity function of single peripheral units; and sensory neocortex and the evolution of intellig.